CULTIVO ORGÁNICO DE PIMIENTO (Capsicum Annuum) COMO ALTERNATIVA ALIMENTICIA EN HUERTOS FAMILIARES - BERMUDEZ PEÑA, SANTIAGO KELLER (2019)
The present project is developed with the objective of describing the Organic Cultivation of Pepper (Capsicum Annuum) as a food alternative in family gardens, to improve the economic and nutritional conditions of the inhabitants of the sector, this type of crops are carried out through the elaboration of platabandas, which facilitate the control of weeds, irrigation and pests with the purpose of protecting the planting, for this we proceed to the construction of a natural enclosure of cane guadua to avoid external negative impacts; The cultivation work is carried out by preparing the soil, by means of the sowing soil, ash, rice pad, molasses and water, fertilizing the organic fertilizer, in addition to the control of pests the organic insecticide is used, these crops are made of 60 to 100 days, resulting in a product of high nutritional quality, guaranteed for consumption and commercialization. It would be advisable that Ecuadorian families will carry out these organic agricultural work that will improve their nutritional status and economic support